Diverging paths : an examination of the Stout-Ngata recommendations and subsequent legislation : a thesis presented in partial fulfilment of the requirements for Masters of Arts at Massey University - Tuuta, Dion (Massey University, 1996)
In 1907 the Commission on Native Land and Native Land Tenure was created in order to examine the state of Maori owned lands throughout the North Island of New Zealand. The Commission was headed by the Chief Justice, Sir Robert Stout, and Apirana Ngata, and became known as the Stout-Ngata Commission. The Stout-Ngata Commission of 1907-1909 ascertained how much "surplus" Maori land existed throughout the North Island during this time and the best ways to utilise and settle the land in the interests of the Maori owners and the public good. The Commission toured the country interviewing hundreds of Maori owners and relayed their wishes to the government in a series of forty-two reports. The Commission offered the government advice on matters affecting Maori land legislation. The purpose of this thesis is to ascertain the influence of the Stout-Ngata Commission on subsequent Maori land legislation and to highlight the impetus behind the legislation of the time. This will be done by examining the activities of Stout and Ngata throughout the North Island and the recommendations they made to Parliament in regard to the management and development of Maori land. The thesis will then examine three major pieces of Maori land legislation that came in the wake of the Stout-Ngata Commission. A key question is how successful were the recommendations of the Stout-Ngata Commission in influencing this legislation. Responses to the Commission throughout New Zealand were many and varied. In general, European politicians envisioned the Commission's recommendations as an avenue for the opening up of "surplus" Maori lands for European settlement. In general, the Maori members of Parliament were hopeful that the Commission would offer Maori a greater chance to farm and develop their remaining lands. Problems arose with the interpretation of the Commission's reports by government and the eventual translation of the recommendations into legislation. The government, overwhelmingly Pakeha in membership and outlook, pursued an official policy of assimilation. 1. J. Metge, The Maoris of New Zealand. [1967], (London, 1976), p.303. Ideas of European superiority influenced the way Pakeha politicians approached the Commission's recommendations and the framing of Maori land legislation. This created a noticeable gap between the recommendations of the Commission and the legislation subsequently passed.
Keywords: Maori (New Zealand people); Land tenure; History; Government relations